Design of UWB antipodal Vivaldi antenna with rectangular corrugated edges for through wall Imaging (TWI) applications - Ahmed, Sajjad; Joret, Ariffuddin; Katiran, Norshidah; Abdullah, M. F. L.; Zakaria, Zahriladha; Sulong, Muhammad Suhaimi; Osman, Anwar Faizd (2024)
An Ultra-wideband (UWB) rectangular corrugated edges antipodal Vivaldi antenna (RCE-AVA) designed for through wall imaging applications is demonstrated. In this study, two distinct designs for antipodal Vivaldi antennas are reported: a conventional AVA and a rectangular corrugated edges AVA. In this study, a parametric-based analysis of both antennas is presented. At first, a conventional AVA with an elliptical shaped antenna is designed using FR4 substrate. Additionally, the antenna is modified with Rogers-5880 material by implementing same size rectangular corrugations on the edges of the antenna. Furthermore, the modified antenna provides stable gain and high directivity throughout the UWB band. The proposed antenna worked in the frequency range from 3.1 GHz to 10.6 GHz with improved radiation properties. A maximum gain of around 11.8 dB is achieved with a return loss value of less than -10. Computer Simulation Technology (CST) simulation software was used to verify the design, parametric evaluation, and optimization of RCE- AVA